Fluidized bed gasification of eucalyptus chips: Axial profiles of syngas composition in a pilot scale reactor. (15th March 2021) - Parrillo, Francesco; Ardolino, Filomena; Calì, Gabriele; Marotto, Davide; Pettinau, Alberto; Arena, Umberto
Abstract: Air gasification tests have been carried out in a pilot scale bubbling fluidized bed gasifier, able to treat up to 100 kg/h of Eucalyptus wood chips, and operated, under chemical and thermal steady-state conditions, at different values of equivalence ratio. The results are reported in terms of the main process performance parameters and transfer coefficients, which indicate the fate of carbon in the different output streams (syngas, fines, tars). The results can be transferred to commercial scale reactors and confirm the technical feasibility of the air gasification of the biomass in the range 0.25–0.34 of equivalence ratio, yielding a good quality syngas, with a low heating value between 5000 and 6000 kJ/m 3 N, syngas . The measured axial syngas composition profiles along the reactor indicate a monotonic reduction of methane and carbon dioxide concentrations and an increase of that of hydrogen. This suggests that water gas shift and steam and dry reforming reactions play a significant role, together with a limited contribution of tar cracking reactions, probably enhanced by alkali and alkaline earth metallic species contained in the inorganic fraction of elutriated fines. Results can support the implementation of reliable numerical models of bubbling fluidized bed gasifiers and the optimisation of design/operating criteria. Highlights: A pilot scale BFBG gasified Eucalyptus chips under auto-thermal conditions. The main process performance parameters have been measured. Transfer coefficients indicate the fate of carbon in the different output streams. The axial profiles of syngas composition and temperature have been measured. Results can be useful to implement and validate mathematical models of BFBG.